Meaning comes first: languaging and biosemiotics - Cowley, Stephen (Rivista Italiana di Filosofia del Linguaggio, 2022)
In linking evolution, biosemiotics and languaging, analysis of meaning is extended by investigation of natural innovation. Rather than ascribe it to internal or external content, meaning comes first. Ecological, evolutionary and developmental flux defy content/ vehicle distinctions. In the eco-evo-devo frame, I present the papers of the Special Issue, pose questions, and identify a direction of travel. Above all, meaning connects older views of semiosis with recent work on ecosystemic living. Whilst aesthetics and languaging can refer to evolving semiotic objects, nature uses bio-signals, judging experience, and how culture (and Languages) can condition free-living agents. Further, science changes its status when meaning takes priority. While semiotics shows the narrowness of laws and recurrent regularity, function brings semiotic properties to causal aspects of natural innovation. By drawing on languaging one can clarify, for example, how brains and prostheses can serve human cyborgs. Indeed, given a multi-scalar nexus of meaning, biosemiotics becomes a powerful epistemic tool. Accordingly, I close with a model of how observers can use languaging to track both how self-fabricated living systems co-modulate and also how judging (and thinking) shapes understanding of changing ‘worlds.’ In certain scales, each ’whole’ agent acts on its own behalf as it uses epigenetic history and adjusts to flux by engaging with an ecosystem